QUALITY OF LIFE OF PATIENTS WITH LEPROSY REACTIONS - Siméia Macêdo de Lima; Karen Krystine Gonçalves de Brito; Emanuelle Malzac Freire de Santana; Matheus de Medeiros Nóbrega; Paula Soares Carvalho; Simone Helena dos Santos Oliveira; Mirian Alves da Silva (Universidade Federal do Paraná, 2019)
Purpose: To evaluate the impact of leprosy on the quality of life of patients with leprosy reactions. Method: A cross-sectional and quantitative study of 40 patients in January 2017 at a referral outpatient clinic in Paraíba using a questionnaire containing sociodemographic and clinical-epidemiological data and an instrument for quality of life assessment, The World Health Organization Quality of Life. Results: It was observed that the dimension of social relations stood out (64.38) with a better score for quality of life, highlighting the high satisfaction (85%) of the individuals. The physical domain presented the lowest score (51.07), with 50% of reports of limitation to perform activities due to pain, but all dimensions scored above 50 points, leading to a good quality of life. Conclusion: The pathophysiology of reactions, living conditions and health policies can influence the quality of life of patients, reflecting on the need to foster public policies for this population.